Replication-dependent activation of the adenovirus major late promoter is mediated by the increased binding of a transcription factor to sequences in the first intron. - Jansen-Durr, P (J Virol, 1989)
During lytic infection, the adenovirus major late promoter (MLP) is primarily activated after the onset of viral DNA replication. Using a combination of DNA binding and in vitro transcription assays, we delineated a discrete MLP element spanning positions +80 to +106 which is essential for the replication-dependent activation of this promoter. We also identified a 40-kilodalton protein (the downstream element factor [DEF]) which binds to the +86-TTGTCAGTTT-+95 motif within this element. Whereas the DEF-binding activity is barely detectable in uninfected cells, it is readily visualized in adenovirus-infected cells, but only after the onset of viral DNA replication. Preventing the interaction of DEF with the MLP template impairs the in vitro transcriptional stimulation. We conclude that this replication-dependent activation of the MLP is, at least in part, mediated by induction of the specific binding of DEF to the MLP downstream element. IMAGES: